Laminar Flow and Heat Transfer in a Square Channel Installed with Inclined Wavy Surface - Amnart Boonloi; Withada Jedsadaratanachai (My University, 2017)
Laminar flow and heat transfer characteristic in a square channel heat exchanger installed with inclined wavy surface are investigated numerically. The inclined wavy surface is designed with the main the aim to help the installation, production and maintenance when using the inclined wavy surface in the heat exchanger. The finite volume method with SIMPLE algorithm is selected to solve the present problem. The effects of flow attack angle (α = 15°-60°) and Reynolds number (Re = 100-1200) on heat transfer, friction loss and thermal performance are considered. The numerical model is validated with the smooth channel. The grid independence of the computational domain is checked. The numerical results show that the heat transfer enhancement is around 1.9-7.5 times above the smooth channel. The optimum thermal performance is found at the flow attack angle of 45° around 2.35 at Re = 1200.
Keywords: Heat transfer enhancement; Square (algebra); Heat Transfer Mechanisms